Rotational strength, range of motion, and function in people with unaffected shoulders from various stages of life - Roy Jean-Sébastien; MacDermid Joy C; Boyd Kirsty; Faber Kenneth J; Drosdowech Darren; Athwal George S (BMC, 2009)
Abstract Background Different measurements are used to assess shoulder function, including range of motion, strength, functional performance and self-report function. To understand disablement, it is necessary to understand the relationship between impairments and function in persons without shoulder problems. This study was conducted to enhance existing comparative data in subjects without upper extremity pathology, and to assess the relationships between impairments (range of motion, strength) and self-reported or measured function/disability. The impact of age, gender and dominance was determined. Methods Two-hundred ninety-four subjects with unaffected shoulders were recruited. The subjects (mean age: 37 years old) were divided into three subgroups, 18-39, 40-59, and over 60 years of age. During a single session, at least two of the following variables were measured: self-reported function (shoulder disability scales), range of motion, isometric rotational strength, or upper limb functional performance (FIT-HaNSA). Two-way analysis of variance was used to determine, for each variable, the effects of age and gender. The relationship between the outcomes was established using Pearson product correlations. Results Men were significantly stronger than women for all age categories. There was an age-related decline in strength in men in the over-60 age category. Significant negative correlations between strength and range of motion were demonstrated (-0.22 <r < -0.32). Women had a significantly higher range of motion than men for external rotation in the 40-59 age category. Furthermore, the subjects in the over-60 age category experienced a decrease of range of motion. There was minimal disability reported in all age groups on self-report scales. Only the Simple Shoulder Test demonstrated significant decreases in the over-60 age category and correlated with age (r = -0.202). Conclusion Self-reported disability was low in individuals without upper extremity problems, although recruitment of such individuals was difficult in the older age groups due to the high prevalence of shoulder pathology. A low correlation between self-report disability and strength/range of motion in these unaffected subjects reflects the lack of disability reported by all subjects without pathology despite normal variations in strength and motion.